Zn as the Factor of Alkaline Phosphatase in Periodontal Patients consuming Minangkabau food in West Sumatra, Indonesia (Bangladesh Journal of Medical Science, 2019)
Background: Periodontal disease is preceded by an inflammation in the gingiva surrounding the teeth called gingivitis. It is an untreated gingivitis causing hard tissue damage (alveolarbone). This inflammation increases the activity of ALP enzyme. Zinc is an Alkaline Phosphatase co-factor.Aim: This study aims at proving the connection between Alkaline Phosphatase (ALP) and zinc within the food of the Minangkabau people in West Sumatra, Indonesia. 60 samples are involved in this study. ALP level is tested by using ELISA technique. Zinc level in Minangkabau food is measured by Food Frequency Questionnaire (FFQ). Data is analyzed by means of univariate to describe each variable , Kolmogorov Smirn of Test is used to see the normal distribution ( p > 0.05).Result: Pearson correlation is conducted to see the correlation between ALP level and zinc clevel in Minangkabau food. The study reveals that ALP activity is higher in mild periodontitis compared to mild gingivitis and healthy control. Zinc level is significantly lower in mild periodontitisthanin mild gingivitis and healthy control individuals. The relation between ALP and zinc level indicates strong correlation with positive direction (r = - 0,884).Conclusion: Zn decreases ALP activity and shows that zinc complement has both preventive and curing effects in periodontitis patients.Bangladesh Journal of Medical Science Vol.18(2) 2019 p.228-232